(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
With the increasing enrollment of students in the regular higher education makes it necessary a deep reflection about education, mainly on what refers to attractive methodologies for these students. It is still notorious that higher education has as its main objective to promote for these students the perception of similar professional life, and also prepares for the workday, considering the obstacles that they may experience. Thereby, it is evident what was exposed above became a challenge for some institutions, once the methodology applied in the course uses only theories, and are not presented in a practical way. In order to create a didactic and dynamic materials to assist in practical activities in the course of Civil Engineering at the Federal University of Jequitinhonha and Mucuri Valleys (UFVJM), the present work has the objective the measurement of a hydrosanitary installation and the construction of a movable didactic panel, which simulates residential bathroom installations. The project has been dimensioned in accordance with current Brazillian standards for cold water, hot water, sewer and electrical installations. Thus, the mobile educational unit will contribute to the dissemination of knowledge about the hydrosanitary installations to UFVJM students in the Mucuri campus, and the entire community in the region.